A new preventive intervention for children of substance‐abusing parents: Results of a randomized controlled trial. Issue 4 (21st February 2019) - Bröning, Sonja; Sack, Peter‐Michael; Haevelmann, Andrea; Wartberg, Lutz; Moesgen, Diana; Klein, Michael; Thomasius, Rainer
Abstract: Children of substance‐abusing parents (COS) are at risk for developing psychosocial problems. We evaluated the effectiveness of the manualized, 9‐session psycho‐educational preventive intervention "TRAMPOLINE" (PE) for 8–12‐year‐old COS compared with a non‐educational "fun and play" group (NE) of equal length delivered by social workers in 27 German counselling centres. A randomized controlled trial was conducted to compare PE ( n  = 130) and NE ( n  = 88) outcomes at baseline, post intervention, and 6‐month follow‐up. Primary outcomes were related to stress and coping; secondary were also examined. Analyses were conducted using baseline‐adjusted repeated measures linear mixed models. Five outcomes revealed improvements both in PE and NE, four of which were more pronounced in PE, and one more pronounced in NE. Small but significant group differences in favour of PE were found in "social isolation" and "addiction‐related knowledge." Children from both groups reported reduced mental distress, reduced avoidance in coping with family stress, improved self‐perceived autonomy, and a better parent–child relationship. No changes were observed in self‐efficacy, physical stress symptoms, and in other health‐related quality of life aspects. TRAMPOLINE can instill positive changes in COS by reducing mental distress and social isolation.